FINANCIAL PERFORMANCE ANALYSIS USING ACTIVITY RATIOS AT PT. ADHI KARYA PERSERO TBK LISTED ON THE INDONESIAN STOCK EXCHANGE (BEI) 2021-2022 - Amru Usman; Melisa; Alya Azhara; Salsabila; Putri Sri Delviani (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
Financial statement analysis is the process of studying trends in financial position to determine considerations for the company's future development. The aim of this research is to determine the results of the activity ratio analysis of the financial performance of construction companies, EPC, property, real estate, infrastructure investment, PT. Adhi Karya Persero Tbk. The data analysis method is qualitative. The research results increased activity ratios, such as receivable turnover, from 4.22 in 2021 to 4.54 in 2022 at PT. Adhi Karya Persero Tbk shows that companies can collect receivables more efficiently. This can indicate better management in managing a company's assets and liquidity, which can have a positive impact on cash flow and overall financial health.